Light axiodilatons: matter couplings, weak-scale completions and long-distance tests of gravity - Brax, Philippe; Burgess, C.P.; Quevedo, F. (Journal of cosmology and astroparticle physics, 2023)
We consider the physical implications of very light axiodilatons motivated by a novel mechanism to substantially reduce the vacuum energy proposed in 2110.10352 . We address the two main problems concerning the light axiodilaton that appears in the low-energy limit, namely that the axion has a very low decay constant f a ∼ eV (as read from its kinetic term) and that the dilaton is subject to bounds that are relevant to tests of GR once ρ vac ≲ 10 -80